Is this child sick? Usefulness of the Pediatric Assessment Triangle in emergency settings - Ana Fernandez; Javier Benito; Santiago Mintegi (Brazilian Society of Pediatrics, 2017)
Objective: The Pediatric Assessment Triangle is a rapid assessment tool that uses only visual and auditory clues, requires no equipment, and takes 30-60 s to perform. It's being used internationally in different emergency settings, but few studies have assessed its performance. The aim of this narrative biomedical review is to summarize the literature available regarding the usefulness of the Pediatric Assessment Triangle in clinical practice. Sources: The authors carried out a non‐systematic review in the PubMed®, MEDLINE®, and EMBASE® databases, searching for articles published between 1999-2016 using the keywords "pediatric assessment triangle," "pediatric triage," "pediatric assessment tools," and "pediatric emergency department." Summary of the findings: The Pediatric Assessment Triangle has demonstrated itself to be useful to assess sick children in the prehospital setting and make transport decisions. It has been incorporated, as an essential instrument for assessing sick children, into different life support courses, although little has been written about the effectiveness of teaching it. Little has been published about the performance of this tool in the initial evaluation in the emergency department. In the emergency department, the Pediatric Assessment Triangle is useful to identify the children at triage who require more urgent care. Recent studies have assessed and proved its efficacy to also identify those patients having more serious health conditions who are eventually admitted to the hospital. Conclusions: The Pediatric Assessment Triangle is quickly spreading internationally and its clinical applicability is very promising. Nevertheless, it is imperative to promote research for clinical validation, especially for clinical use by emergency pediatricians and physicians.